Discipline Culture Development at Thayaiwittaya School Khuang Lang Hatyai Songkhla Southern Thailand - Rita Pusvitasari (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
The study analyzes disciplinary culture in elementary schools. A discipline is a form of human morality. Discipline is a value related to self-control against the rules that apply in society. Discipline is expected to form good morals and order in society. Students with discipline will be able to have a positive influence on life after they leave the education level and the discipline will grow into provisions in the future. The research used a qualitative approach to the type of case study. Data collection techniques were carried out through; observation, interview, and documentation. Furthermore, the research data is presented in a descriptive narrative form. The results of the study show that setting an example for students by performing the Zuhur and Asr prayers together, motivates students to take part in extracurricular activities to improve skills and train discipline, give advice, carry out class pickets, and provide motivation that is inserted in every lesson. times of opportunity, and provide warnings or punishments.